Arts, secular ritual, and health: combining (micro)sociology and the social cure to link the arts to health through interaction ritual - Warran, Katey (Frontiers in Social Psychology, 2025)
Despite the early roots of arts and health as grounded within rituals and interest in ”community”– a term that is deeply laden with a history of rituals - the role of ”ritual” in modern arts and health is largely untheorized. Yet, ”secularized” rituals can teach us about contemporary life, beliefs, and practices, playing a role in our understanding of how and why the arts connect to health and wellbeing. In this article, I draw on published literature and insights from my experiences in the field of arts and health to make the case that incorporating “ritual” as a concept within arts and health research serves to expand existing thinking in social psychology. Specifically, I link Interaction Ritual Chain (IRC) theory and the social cure approach (a social identity approach to health) to theorize that arts activities may enable the construction of group identities through participation in interaction rituals, whereby ritual outcomes across chains of interactions may be considered as expressions of health and wellbeing. The article makes an original contribution to social psychology by connecting IRC theory to a social identity approach to health, laying a new theoretical foundation for researchers working in arts and health.